Addressing TB-related mortality in adults living with HIV: a review of the challenges and potential solutions. (March 2022) - Sullivan, Amanda; Nathavitharana, Ruvandhi R.
Tuberculosis (TB) is the leading cause of death in people living with HIV (PLHIV) globally, causing 208, 000 deaths in PLHIV in 2019. PLHIV have an 18-fold higher risk of TB, and HIV/TB mortality is highest in inpatient facilities, compared with primary care and community settings. Here we discuss challenges and potential mitigating solutions to address TB-related mortality in adults with HIV. Key factors that affect healthcare engagement are stigma, knowledge, and socioeconomic constraints, which are compounded in people with HIV/TB co-infection. Innovative approaches to improve healthcare engagement include optimizing HIV/TB care integration and interventions to reduce stigma. While early diagnosis of both HIV and TB can reduce mortality, barriers to early diagnosis of TB in PLHIV include difficulty producing sputum specimens, lower sensitivity of TB diagnostic tests in PLHIV, and higher rates of extra pulmonary TB. There is an urgent need to develop higher sensitivity biomarker-based tests that can be used for point-of-care diagnosis. Nonetheless, the implementation and scale-up of existing tests including molecular World Health Organization (WHO)-recommended diagnostic tests and urine lipoarabinomannan (LAM) should be optimized along with expanded TB screening with tools such as C-reactive protein and digital chest radiography. Decreased survival of PLHIV with TB disease is more likely with late HIV diagnosis and delayed start of antiretroviral (ART) treatment. The WHO now recommends starting ART within 2 weeks of initiating TB treatment in the majority of PLHIV, aside from those with TB meningitis. Dedicated TB treatment trials focused on PLHIV are needed, including interventions to improve TB meningitis outcomes given its high mortality, such as the use of intensified regimens using high-dose rifampin, new and repurposed drugs such as linezolid, and immunomodulatory therapy. Ultimately holistic, high-quality, person-centered care is needed for PLHIV with TB throughout the cascade of care, which should address biomedical, socioeconomic, and psychological barriers.